Security Protocols XIX 19th International Workshop, Cambridge, UK, March 28-30, 2011, Revised Selected Papers - Christianson, Bruce; Crispo, Bruno; Malcolm, James; Stajano, Frank; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the 19th International Workshop on Security Protocols, held in Cambridge, UK, in March 2011. Following the tradition of this workshop series, each paper was revised by the authors to incorporate ideas from the workshop, and is followed in these proceedings by an edited transcription of the presentation and ensuing discussion. The volume contains 17 papers with their transcriptions as well as an introduction, i.e. 35 contributions in total. The theme of the workshop was "Alice doesn't live here anymore".
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Computers and Society